Studies on proton exchange membranes-based SPEEK Chitosan crosslinked via ultraviolet curing method / Nazli Ahmad Aini - Ahmad Aini, Nazli (Institute of Graduate Studies, UiTM, 2018)
The use of proton exchange membrane (PEM) is very significant component in PEMFC and DMFC. It functions to separate anode and cathode, prevents fuel gas crossover, and transports protons from anode to the cathode through it. Nation is widely used as a PEM material in commercial PEMFC due to high proton conductivity, good mechanical, chemical stability and excellent thermal stability. However, seeking for new materials as an alternative to Nation is needed due to its expensive, low proton conductivity when temperature operation above 100 oC and high fuel permeability. As an alternative, sulfonated poly(ether ether ketone) (SPEEK) based membrane is a potential candidate due to low cost, exhibit good chemical and thermal stabilities. However, SPEEK with high degree of sulfonation (DS) exhibits gradually deterioration of the mechanical properties, excessive water uptakes at elevated temperatures and methanol permeability that leads to the reduction in cell voltage performance. The use of hybrid membrane is one opportunity to overcome the SPEEK drawbacks. SPEEK and Chitosan can be crosslinked through sulfonic (-S03H) and amine (-NH2) functional groups. Introduction of Chitosan into SPEEK membrane can modify SPEEK properties particularly by improving its swelling ability. Several series of cross-linked membranes of SPEEK with a chitosan were prepared by solution cast technique. SPEEK and Chitosan was dissolved in DMSO and acetic acid, respectively. They were then mixed together and stirred until homogenous solution obtained. The solution was then exposed and treated under ultra violet (UV) light for curing process. Only six samples were prepared with different composition…